2010
DOI: 10.1590/s0066-782x2010005000035
|View full text |Cite
|
Sign up to set email alerts
|

Controle da pressão arterial em pacientes sob tratamento anti-hipertensivo no Brasil: Controlar Brasil

Abstract: Artículo recibido el 08/04/09; revisado recibido el 05/11/09; aceptado el 18/11/09. ResumenFundamento: El control de la presión arterial (PA) es fundamental en la hipertensión arterial (HA).Objetivo: Conocer el porcentaje de pacientes que requieren metas específicas de control de la PA, atendidos en consultorios en Brasil.Métodos: Cada investigador, en número de 291, debería evaluar, por medición convencional de la PA, en cinco días consecutivos, los dos primeros pacientes atendidos. Se determinó el número de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 16 publications
3
6
1
10
Order By: Relevance
“…Low control rates are related with an inappropriate approach of the clients, ineffective treatment, low treatment adherence, difficulty to access the services and purchase the drugs. (3,15) In this study, no statistically significant association was found between lack of blood pressure control and sociodemographic characteristics. The results are in accordance with the literature, which appoints a higher prevalence of uncontrolled blood pressure among younger people, (16) with a higher education level, (4,13,17) lower income, (4,13) and without a partner.…”
Section: Discussioncontrasting
confidence: 53%
“…Low control rates are related with an inappropriate approach of the clients, ineffective treatment, low treatment adherence, difficulty to access the services and purchase the drugs. (3,15) In this study, no statistically significant association was found between lack of blood pressure control and sociodemographic characteristics. The results are in accordance with the literature, which appoints a higher prevalence of uncontrolled blood pressure among younger people, (16) with a higher education level, (4,13,17) lower income, (4,13) and without a partner.…”
Section: Discussioncontrasting
confidence: 53%
“…The intervention performed increased significantly adherence rates among patients when assessed by both the self-reported adherence and the Morisky-Green test. These findings were in agreement with studies (Skowron, Polak, Brandys, 2011;Nobre, Ribeiro, Mion, 2010;Sociedade Brasileira de Cardiologia, 2010;Prado, Kupek, Mion, 2007;Lyra et al, 2007) showing that pharmaceutical interventions intended to increase motivation and adherence to treatment help improve medication adherence.…”
Section: Discussionsupporting
confidence: 90%
“…In a study conducted by Nobre, Ribeiro and Mion on blood pressure control in Brazil (Nobre, Ribeiro, Mion, 2010), the number of patients with controlled blood pressure was similar to that found in this study before the intervention. Analysis of blood pressure readings before and after the intervention revealed that pharmaceutical intervention improved control of blood pressure, which is in agreement with the 6 th Brazilian Guidelines on Hypertension (Sociedade Brasileira de Cardiologia, 2010), meaning that adherence to treatment changes the disease control (Skowron, Polak, Brandys, 2011;Vrijens et al, 2008;Silva et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…Only Sousa et al 13 found a similar rate (40.9%) in a study carried out in a small municipality in the South of Brazil. Nobre et al 23 found a slightly higher proportion of patients with wellcontrolled hypertension (46.5%) ; however, this study was conducted in specialized cardiological centers. The proportion of diabetics with blood pressure below the recommended threshold for type 2 diabetes was 25.8%, showing that blood pressure control was much less satisfactory in diabetic subjects.…”
Section: Discussionmentioning
confidence: 68%